2020
DOI: 10.1055/s-0040-1707286
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Carboxylic Acids and Their Derivatives with P(O)–H Compounds Forming P(O)–C Bonds

Abstract: Herein, we highlight advances in the phosphorylation of readily available carboxylic acids and their derivatives forming synthetically important P(O)–sp3C, P(O)–sp2C, and P(O)–spC bonds, with an emphasis on the results demonstrated since 2010. This review examines the challenges associated with the use of this strategy for the synthesis of organophosphorus compounds and details advances in the design of catalytic systems that suppress these problems thus resulting in notable progress. Mechanistic details are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Besides, once 4h was isolated and subjected to the standard reaction conditions of this study, the target product 3h was obtained in 81% yield (Scheme 4b). This result is consistent with the report by Rueping on the synthesis of sulfides from thioesters 18 by a similar nickel-catalyzed decarbonylation reaction. 7g Based on the results of the relevant mechanistic studies obtained above, the catalytic cycle for this reaction is proposed as shown in Scheme 5.…”
Section: Special Topic Synthesissupporting
confidence: 93%
“…Besides, once 4h was isolated and subjected to the standard reaction conditions of this study, the target product 3h was obtained in 81% yield (Scheme 4b). This result is consistent with the report by Rueping on the synthesis of sulfides from thioesters 18 by a similar nickel-catalyzed decarbonylation reaction. 7g Based on the results of the relevant mechanistic studies obtained above, the catalytic cycle for this reaction is proposed as shown in Scheme 5.…”
Section: Special Topic Synthesissupporting
confidence: 93%
“…Recently, numerous research groups have found that redox-active esters are more reactive than alkyl iodides and provide alkyl radicals via single-electron reduction followed by decarboxylation with the release of a non-nucleophilic leaving group. 11 Pleasingly, irradiation of 1a ( E 1/2 = −1.23 V vs. SCE of 1a) 10 in MeOH provided the desired ring-expansion product 2a with 40% yield ( Scheme 2 ). 12 A substantial increase in the reaction yield was observed by employing more reducing photocatalysts, probably due to the more favourable single-electron transfer between the excited state Ir III and redox-active ester 1a ( Table 1 , entries 2–4).…”
Section: Resultsmentioning
confidence: 99%